The U.S. Navy and its Cold War alliances, 1945-1953 - Williamson, Corbin (Modern war studies., 2020)
"In the aftermath of World War II, the US Navy turned away from 150 years of traditional American foreign policy by forming alliances with its closest wartime allies: the British, Canadian, and Australian navies. In contrast to historians who have cast the early Cold War US Navy as overly nationalistic and uninterested in cooperation with allies, Corbin Williamson shows that American officers and officials worked to maintain wartime levels of interoperability with the British, Canadian, and Australian navies. Concerned about the growing threat posed by the Soviet Union, these four navies built a web of informal links and connections: personnel exchanges, standardization efforts in equipment and doctrine, combined training and education, and planning for a war with the Soviets. Political concerns, especially in the United States, kept these navy-to-navy links out of the public sphere. Using a "history from the middle" approach, Williamson focuses on the actions of mid-level officials and officers who managed and maintained these informal alliances on a day-to-day basis, drawing upon official and private papers from archives in all four nations, including large numbers of recently declassified documents."--.